0
$\begingroup$

Solve : $$\lim\limits_{n \to \infty}\frac{sgn(n^2-3n+2)}{e^{n+1}}$$ Now, i started by applying the quotent rule $\frac{\lim\limits_{n \to \infty} sgn(n^2-3n+2)}{\lim\limits_{n \to \infty}e^{n+1}}$. The second limit gives out infinity . I do have a problem with the first limit : $sgn(\lim\limits_{n \to \infty}(n^2-3n+2))$ and then $sgn(\infty)$ which i am not sure how to evaluate . Wolfram says the answer is 0 .I just want an explanation for the first limit ( the one with the sign function ).

$\endgroup$
  • 1
    $\begingroup$ for the signum part, you have to know, that this part is bounded by $1$. $\endgroup$ – Fakemistake Mar 17 at 10:41
3
$\begingroup$

Try the squeeze theorem:

$$0\xleftarrow[n\to\infty]{}\frac{-1}{e^{n+1}}\le\frac{\text{sgn}(n^2-3n+2)}{e^{n+1}}\le\frac1{e^{n+1}}\xrightarrow[n\to\infty]{}0$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Do you think we can take $(-1)^n$ instead of that $\text{sgn}$? $\endgroup$ – mrs Mar 17 at 10:51
  • $\begingroup$ @mrs No, In each side that's exactly the sigh. Now, if you don't want to use the squeeze theorem but, say, the theorem that says that bounded times converging to zero is converging to zero then the answer is yes. $\endgroup$ – DonAntonio Mar 17 at 12:26
  • 1
    $\begingroup$ Thanks my dear old friend! $\endgroup$ – mrs Mar 17 at 17:46
2
$\begingroup$

When $n \to \infty, n^2-3n+2 \sim n^2,~ so ~ sgn(n^2-3n+2)=+1$ So the required limit is $$L=\lim_{n \to \infty} \frac{sgn(n^2-3n+2)}{e^{n+1}}=\frac{1}{\infty}=0$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.